2021
DOI: 10.1007/s11077-021-09436-0
|View full text |Cite
|
Sign up to set email alerts
|

Reap what you sow: implementing agencies as strategic actors in policy feedback dynamics

Abstract: Government agencies responsible for policy implementation have expertise on policy practicability, efficiency and effectiveness, and knowledge which is provided to policymakers as feedback. However, we know very little about the feedback dynamics in which implementing agencies provide different types of feedback with the intention that it is used by policymakers, and the strategic decisions underlying these dynamics. This article connects the literature on policy feedback and knowledge use to develop a typolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Although, looking at formal structures for involving multiple stakeholders evidence in this direction is lacking. This may imply that successful stakeholder engagements can still occur through informal venues (see, for example, Polman and Alons, 2021). Moreover, stakeholder involvement may still play a role in enabling high innovativeness; however, our findings indicate that in combination with the investigated governance tools this cannot offer a sufficient explanation.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…Although, looking at formal structures for involving multiple stakeholders evidence in this direction is lacking. This may imply that successful stakeholder engagements can still occur through informal venues (see, for example, Polman and Alons, 2021). Moreover, stakeholder involvement may still play a role in enabling high innovativeness; however, our findings indicate that in combination with the investigated governance tools this cannot offer a sufficient explanation.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…Therefore, our findings could demonstrate that the resource effect of e‐governance infrastructure is counteracted by individuals' privacy concerns regarding the health QR code, resulting in a non‐significant relationship with their acceptance of this technology. In addition, recent studies have shown that the feedback of a policy goes beyond the distinction between positive and negative (Daugbjerg & Kay, 2020 ; Polman & Alons, 2021 ), meaning that the ultimate feedback may contain conflicting formation paths. We believe the inconsistent results regarding the resource effect and interpretive effect demonstrate the complexity of the overall policy feedback effect.…”
Section: Discussionmentioning
confidence: 99%
“…Historical institutionalist scholars have long suggested that individuals' opinions and behaviors are shaped by institutions (Pierson, 1993 ; Skocpol, 1992 ; Steinmo et al, 1992 ). Within policy science, the policy feedback literature views past policies as “causes” and has elaborated upon the effects and mechanisms through which public policies shape citizens' behavior in the policy process (e.g., Fernández & Jaime‐Castillo, 2013 ; Polman & Alons, 2021 ; Schmid et al, 2020 ). Following this line of thought, the present study aims to explore the roles of past policies in the formulation of citizens' acceptance of ICTs.…”
Section: Introductionmentioning
confidence: 99%
“…Johanson (2009), for instance, explores various aspects of strategizing, placing emphasis on the role of public agencies in strategic planning. Similarly, Polman and Alons (2021) investigate public agencies responsible for policy implementation, aligning more closely with the focus of this study, development of strategy at a higher level (European Commission), with the implementation occurring at a lower level of government. Developing a strategy for a subject differs significantly from a unit strategy, further complicated by the division between formulators and implementers, opening for example the door to a principal-agent problem.…”
Section: Strategic Planning In Public Administrationmentioning
confidence: 99%